MENTAL HEALTH CARE REFORM IN AFGHANISTAN - Ventevogel, Peter; Azimi, Sayed; Jalal, Sayed; Kortmann, Frank (Journal of Ayub Medical College Abbottabad, 2007)
The mental health situation in Afghanistan is characterized by a highly felt need and an extremely incapacitated mental health care system. The new Afghan government has identified mental health as one of five health priorities. Integration of mental health into the basic health care services of Afghanistan could substantially increase the effectiveness of mental health services. The Afghan government collaborates with non-governmental organisations to rapidly expand basic (mental) health services to underserved populations.